Survival trends in childhood chronic myeloid leukaemia in Southern-Eastern Europe and the United States of America. (November 2016) - Karalexi, Maria A.; Baka, Margarita; Ryzhov, Anton; Zborovskaya, Anna; Dimitrova, Nadya; Zivkovic, Snezana; Eser, Sultan; Antunes, Luis; Sekerija, Mario; Zagar, Tina; Bastos, Joana; Demetriou, Anna; et al.
Abstract: Aim: To assess trends in survival and geographic disparities among children (0–14 years) with chronic myeloid leukaemia (CML) before and after the introduction of molecular therapy, namely tyrosine kinase inhibitors (TKIs) in Southern-Eastern European (SEE) countries and the USA. Methods: We calculated survival among children with CML, acute lymphoblastic (ALL) and acute myeloid leukaemia (AML) in 14 SEE (1990–2014) cancer registries and the U.S. Surveillance, Epidemiology and End Results Program (SEER, 1990–2012). We used Kaplan–Meier curves and multivariate Cox regression models to calculate hazard ratios (HRs) with 95% confidence intervals (CIs). Results: Among 369 CML cases, substantial improvements were noted in 2-year survival during the post-TKI (range: 81–89%) compared to pre-TKI period (49–66%; HR: 0.37, 95% CI: 0.23–0.60). Risk of death was three times higher for <5-year-old children versus those aged 10–14 years (HR: 3.03, 95% CI: 1.85–4.94) and 56% higher for those living in SEE versus SEER (HR: 1.56, 95% CI: 1.01–2.42). Regardless of geographic area and period of TKI administration, however, age seems to be a significant determinant of CML prognosis (pre-TKI period, HR0–4y : 2.71, 95% CI: 1.53–4.79; post-TKI period, HR0–4y : 3.38, 95% CI: 1.29–8.85). Noticeably, post-TKI survival in CML overall approximates that for ALL, whereas therapeutic advancements for AML remain modest. Conclusion: Registry data show that introduction of molecular therapies coincides with revolutionised therapeutic outcomes in childhood CML entailing dramatically improved survival which is now similar to that in ALL. Given that age disparities in survival remain substantial, offering optimal therapy to entire populations is an urgent priority. Highlights: Geographic inequalities persist in childhood chronic myeloid leukaemia (CML) survival. Introduction of molecular treatment has reduced by 63% the risk of death from CML. Improved CML survival now approximates that for acute lymphoblastic leukaemia. Poorer prognosis remains among <5-year-old compared to 10–14 year-old CML children. Offering optimal treatment at population level is an urgent priority.